Analisis Keuangan Untuk Mengukur Kinerja Keuangan Pada Perusahaan Semen Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2015 - Anissastia, Nanda; , Eny Kusumawati, SE., MM., AK, CA (2017)
This research was aimed to find out financial performance of cement companies listed at Indonesia stock exchange in period 2010-2015 if seen from financial ratio analysis, to find out financial performance progress of cement companies listed at Indonesia stock Exchange in period 2010-2015 if seen cross-section and time-series technique, and to find out financial performance progress of PT Semen Indonesia (Persero)Tbk in period 2010-2015 if seen from commonsize analysis and indeks/trend analysis. This research used a sample cement companies listed at Indonesia stock exchange in period 2010-2015. Sample selection using purposive sampling technique and the criteria (1) cement companies listed atIndonesia stock exchange in period 2010-2015 (2) release an annual report for research period by cement companies. From a sample selection, obtainable three cement companies as a sample. This research use secondary data, an annual report from www.idx.co.id and download from each cement companies profile. Result of this research indicate the best financial performance than other cement companies is PT Indocement Tunggal Prakarsa Tbk if seen from financial ratio analysis and cross-section technique. Based from time-series technique, the best financial performance PT Semen Indonesia (Persero) Tbk in 2010, the best financial performance PT Holcim Indonesia Tbk in 2012, and the best financial performance PT Indocement Tunggal Prakarsa Tbk in 2011. Based from commonsize analysis PT Semen Indonesia (Persero) Tbk can push a cost, manage an asset and add a weath, and have a good financial performance. Last, based from indeks/trend analysis PT Semen Indonesia (Persero) Tbk can push a cost, manage a credit and stock, and have a good financial performance. Keyword: Financial performance, Financial ratio analysis, Cross-section technique, Time-series technique, Commonsize analysis, Indeks/trend analysis